2015
DOI: 10.1787/5jrxv0fctk7j-en
|View full text |Cite
|
Sign up to set email alerts
|

Limits to government debt sustainability

Abstract: By Jean-Marc Fournier and Falilou Fall OECD Working Papers should not be reported as representing the official views of the OECD or of its member countries. The opinions expressed and arguments employed are those of the author(s).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 17 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…However, Reinhart et al (2003) suggested a 15%-20% ratio of debt to GDP. Another strand of literature used the FRF to measure public debt sustainability (see Abiad and Baig 2005;Islam and Biswas 2006;De Mello 2008;Hajdenberg and Romeu 2010;Burger et al 2011;Ghosh et al 2013;Fournier and Fall 2015;Campos et al 2020). In addition, to recognize fiscal fatigue risks, Checherita-Westphal and Ždárek (2017) used the FRF to find primary balance benchmarks.…”
Section: Review Of the Empirical Literaturementioning
confidence: 99%
“…However, Reinhart et al (2003) suggested a 15%-20% ratio of debt to GDP. Another strand of literature used the FRF to measure public debt sustainability (see Abiad and Baig 2005;Islam and Biswas 2006;De Mello 2008;Hajdenberg and Romeu 2010;Burger et al 2011;Ghosh et al 2013;Fournier and Fall 2015;Campos et al 2020). In addition, to recognize fiscal fatigue risks, Checherita-Westphal and Ždárek (2017) used the FRF to find primary balance benchmarks.…”
Section: Review Of the Empirical Literaturementioning
confidence: 99%
“…Second, unlike existing studies on public debt sustainability (Bohn, 1998(Bohn, , 2005Fournier & Fall, 2015;Ghosh et al, 2013), and following Beqiraj et al (2018), this study distinguishes between structural (discretionary fiscal policy) and nonstructural primary balance. The discretionary fiscal policies are quantitatively measured by the structural primary balance.…”
Section: Empirical Contribution To Extant Studiesmentioning
confidence: 99%
“…When estimating Equation 1, most of the existing literature (Bohn, 1998(Bohn, , 2005Fournier & Fall, 2015;Ghosh et al, 2013;Mauro et al, 2015) did not distinguish between discretionary fiscal policy response (structural) and automatic fiscal response (nondiscretionary). In contrast, this study follows Beqiraj et al (2018) to distinguish between the discretionary and automatic responses of the primary balance of government actions.…”
Section: Model Specification On the Sustainability Of Public Debt And...mentioning
confidence: 99%
“…For instance, the notion of "fiscal fatigue" has been introduced by Gosh et al (2013) who detect a reversal in the behaviour of the primary balance as debt ratios become very high and the response peters out and becomes negative. Other applications in this direction are by Checherita-Westphal and Zdarek (2017) as well as Fournier and Fall (2015), Legrenzi and Milas (2011) and Owusu et al (2021) for instance.…”
Section: Introductionmentioning
confidence: 99%